A study of Shanghai's development strategy to 2020. Issue 2 (2nd May 2013) - Wang, Yizhi; Shibusawa, Hiroyuki; Leman, Edward; Higano, Yoshiro; Mao, Guoping; Kourtit, Karima; Nijkamp, Peter; Partridge, Mark D.
Abstract Shanghai is the largest economic city in China. Its rapid emergence as a post‐industrial metropolis is causing fundamental shifts in the city's economy. The development trends of Chinese economy need Shanghai to become a global metropolis. This study presents Shanghai's development direction to 2020, shows some key issues facing Shanghai to become a global metropolis, and puts forward some policy recommendations in order to overcome these issues.